Pengaruh Social Media Marketing, Inovasi Produk, Dan Citra Merek Terhadap Keputusan Pembelian Produk Fashion Lokal Erigo: (Studi Pada Remaja Generasi Z Di Kota Bandar Lampung) - Novandri Ramadhan, Thaariq; Devi, Yulistia (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
This research is motivated by the increasingly dynamic development of fashion and technology, humans are required to act quickly and precisely so as not to lose out in competition. Consumer purchasing decisions regarding a product are basically closely related to consumer behavior within the Company. The formulation of the problem in this research is, do social media marketing, product innovation, and brand image partially and simultaneously influence the decision to purchase Erigo products? How are Erigo's brand image and product purchasing decisions viewed from an Islamic business perspective? The aim of this research is to determine the influence of social media marketing, product innovation, and brand image partially and simultaneously on purchasing decisions for Erigo products and to examine brand image and purchasing decisions for Erigo products from an Islamic business perspective. This research is quantitative research, the population in this research is all Generation Z teenagers in the city of Bandar Lampung. The sample used in this research is probability sampling with a sample of 100 people and data analysis for this research uses SEM model analysis using SmartPLS version 4.0 The partial results of this research are that social media marketing (X1) has no positive and significant effect on purchasing decisions (Y), product innovation (X2) has a positive and significant effect on purchasing decisions (Y), and brand image (X3) has a positive and significant effect on purchasing decisions (Y). The simultaneous results of social media marketing, product innovation, and brand image jointly influence the decision to purchase Erigo products. In the Islamic view, every human being consumes goods or services not only for worldly satisfaction but also for prosperity in the afterlife. Allah also forbids his people from committing losses (tabzir and wasteful).